Impact resistance study on rigid polyurethane foam - M. F. F., Mohamad; Mohamad, Mahmod Abd Hakim; W. A. W., Mat; Ahmad Zaidi, Ahmad Mujahid; K., Noraniah; Mat Zin, Ahmad Faiz; Mustapa, Mohammad Sukri; Rajo Mantari, Muhammad Hanafi Asril (Science Publishing Corporation Inc, 2018)
Polyurethane foam was synthesizes generally using isocyanate and polyol that already mix with the surfactant or catalyst as to aid polymer processing and modify properties of the polymer. Polyurethane can be divided to two types which are flexible foam and rigid foam. Usually, the flexible foam will be used in furniture industry to produce soft furniture cushioning and bedding. Rigid foam generally used for composite structured component and insulation. Main focus of this research is to produce a prediction assessment against penetration resistance of rigid polyurethane foam under specific dynamic load. Evaluation is by using analytical prediction method to evaluate the depth of penetration and energy absorption. The fabricated rigid polyurethane foam was undergoing compression test to obtain its mechanical properties and impact test to verify the prediction model with two significant measurements concerned, impact energy and the penetration depth leave by impactor. The impact speed was set up at 1.5 m/s, 1.7 m/s and 2 m/s. Results of experiment shows variations for depth of penetration and energy absorption to the predicted value from the analytical model. This variation is caused by the specimen’s rigidity disordered during the specimen producing process.